Production of bacterial cellulose using Gluconacetobacter kombuchae immobilized on Luffa aegyptiaca support - Sameeha Syed Abdul Rahman (Nature Portfolio, 2021)
Abstract The present work report for the first time on the production of bacterial cellulose (BC) using natural loofa sponge (Luffa aegyptiaca) as a scaffold for the immobilization of Gluconacetobacter kombuchae. Bacterial cellulose (BC) are recently gained more attention in several fields including biological and biomedical applications due to their outstanding physico-chemical characteristics including high thermal stability, easy biodegradability, good water holding capacity, high tensile strength, and high degree of polymerization. The increase in requirement of alternative method for the enhancement of BC production under economical aspect develops a positive impact in large scale industries. In this study, Luffa aegyptiaca (LA) was introduced in a separate fermentation medium so as to enhance the concentration of BC production by Gluconacetobacter kombuchae. Different process/medium parameters such as initial pH, static/shaking condition, inoculum size, nitrogen source, C/N ratio, supplements (ethanol and acetic acid) were analysed for the production of bacterial cellulose using LA support. The maximum yield of BC was obtained using following condition: culturing condition -shaking; initial pH − 5.5; nitrogen source- yeast extract, C/N ratio – 40 and supplement—ethanol. The characterization of the BC was examined using Fourier Transform Infra-Red spectroscopy and thermo gravimetric analysis. The biofilm formation on the surface of LA was examined by SEM photographs. Thus, implementation of LA as a support in shaking fermentation under suitable medium/process variables enhanced the BC production.